Evaluation of Content and Accessibility of Hand Fellowship Websites. (September 2015) - Silvestre, Jason; Guzman, Javier Z.; Abbatematteo, Joseph M.; Chang, Benjamin; Levin, L. Scott
Background: Graduates of general, orthopedic, and plastic surgery residencies utilize web-based resources when applying for hand fellowship training. The purpose of this study was to evaluate the accessibility and content of hand fellowship websites (HFWs). Methods: Websites of accredited hand surgery fellowships were eligible for study inclusion. HFWs were evaluated for comprehensiveness in the domains of education and recruitment. Website content was correlated with program characteristics via Fisher exact tests. Results: Fifteen plastic, 65 orthopedic, and 1 general surgery hand fellowships were analyzed. Seventy-four hand fellowships maintained an HFW (91 %). HFWs were not found for 3 plastic and 4 orthopedic hand programs (20 versus 6 %, p = 0.118). HFWs provided only half of all analyzed content (54 %—education and 49 %—recruitment). Orthopedic programs had more education content than plastic surgery programs (55 versus 44 %, p =0.030). Programs in the South had more education content than programs in the Northeast (63 versus 47 %, p =0.001), but not more than programs in the West (54 %) or Midwest (55 %). Larger programs with more fellows had greater education content than those with only one fellow (57 versus 49 %, p =0.042). Programs affiliated with top-ranked medical schools had less education content than lower-ranked schools (48 versus 56 %, p =0.045). No differences existed in recruitment content between programs. Conclusions: Most hand surgery fellowships lack readily accessible and comprehensive websites. The paucity of online content suggests HFWs are underutilized as educational resources and future opportunity may exist to optimize these tools.